2012
DOI: 10.4269/ajtmh.2012.11-0454
|View full text |Cite
|
Sign up to set email alerts
|

Use of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry Analysis for Rapid Confirmation of Burkholderia pseudomallei in Septicemic Melioidosis

Abstract: Abstract. Burkholderia pseudomallei was quickly identified from blood cultures collected from septicemic patients by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis using an in-house reference library. This procedure reduced the time to definitive identification by more than 24 hours. This analysis is a useful addition to laboratory methods for early recognition of septicemic melioidosis in non-endemic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Using a supplemented Burkholderia library, Inglis et al identified Burkholderia pseudomallei isolated from blood cultures, reducing time to identification by 24 h (2). Using a supplemented library covering Brucella species, Ferreira et al used MALDI-TOF MS to rapidly identify clinical isolates of Brucella species (3), and using a custom-made Brucella library, Lista et al were able to identify Brucella species to the species level using MALDI-TOF MS (4).…”
mentioning
confidence: 99%
“…Using a supplemented Burkholderia library, Inglis et al identified Burkholderia pseudomallei isolated from blood cultures, reducing time to identification by 24 h (2). Using a supplemented library covering Brucella species, Ferreira et al used MALDI-TOF MS to rapidly identify clinical isolates of Brucella species (3), and using a custom-made Brucella library, Lista et al were able to identify Brucella species to the species level using MALDI-TOF MS (4).…”
mentioning
confidence: 99%
“…Confirmed B. pseudomallei were then transferred to Perth, Western Australia for detailed characterization. Isolates were sent as suspensions of bacteria in sterile water and duplicated in nutrient agar-embedded bacteriology [13][14][15] Confirmed B. pseudomallei were also subjected to biogeographic attribution PCR assays for Yersinia-like fimbrial (YLF) and Burkholderia thailandensis-like flagellum and chemotaxis (BTFC) gene clusters. 16 Molecular epidemiology.…”
Section: Methodsmentioning
confidence: 99%
“…MALDI-TOF mass spectra were analyzed using proprietary software (Biotyper; Bruker Daltonic GmbH, Bremen, Germany), the manufacturer's bacterial database and an extended in-house Burkholderia species reference library. 13 MLST ST profiles were analyzed and displayed using goeBURST with single-locus variants (SLVs) selected. 18 Available STs and country of origin were obtained from the MLST website and details filled in from original descriptions.…”
Section: Methodsmentioning
confidence: 99%
“…In screening analysis of microbial cells the use of these two matrices is common [23][24][25][26][27][28][29][30][31][32]. However, the spectra recorded with different matrices had different distribution of peaks ( Figure 3B, 3C).…”
Section: Spectrometric Evaluation Of Environmental Conditionsmentioning
confidence: 99%